2021
DOI: 10.2220/biomedres.42.239
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TUG1 promotes the osteogenic differentiation of bone marrow mesenchymal stem cells by regulating the AMPK/mTOR/autophagy pathway

Abstract: Promoting the differentiation of bone marrow mesenchymal stem cells (BMSCs) into osteoblasts is an effective strategy against osteoporosis. Long non-coding RNAs are closely implicated in BMSC osteogenic differentiation. The present study explored the expression pattern and biological role of taurine upregulated gene 1 (TUG1) in osteogenic differentiation. The expressions of TUG1 and osteogenic markers following the osteogenic induction of BMSCs were detected. The functional relevance of TUG1 was evaluated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In addition, overexpression of TUG 1 (a lncRNA) increases the LC3II/Ⅰ ratio and the number of autophagosomes, which promotes the osteogenic differentiation of BMSCs. When the TUG 1 is overexpressed, AMPK and p53 are elevated, and level of mTOR is decreased, suggesting that TUG 1 can regulate the AMPK/mTOR/autophagy axis to promote the osteogenic differentiation of BMSCs ( Lu et al, 2021a ). Although the research on lncRNAs and circRNAs is currently limited, existing studies suggest that both have potential roles in regulating autophagy and osteoporosis.…”
Section: Autophagy-relate Ncrnas and Bone Metabolic Diseasesmentioning
confidence: 99%
“…In addition, overexpression of TUG 1 (a lncRNA) increases the LC3II/Ⅰ ratio and the number of autophagosomes, which promotes the osteogenic differentiation of BMSCs. When the TUG 1 is overexpressed, AMPK and p53 are elevated, and level of mTOR is decreased, suggesting that TUG 1 can regulate the AMPK/mTOR/autophagy axis to promote the osteogenic differentiation of BMSCs ( Lu et al, 2021a ). Although the research on lncRNAs and circRNAs is currently limited, existing studies suggest that both have potential roles in regulating autophagy and osteoporosis.…”
Section: Autophagy-relate Ncrnas and Bone Metabolic Diseasesmentioning
confidence: 99%
“…The expression of TUG1 increased during the differentiation of BMSCs into OBs, while in TUG1-silenced BMSCs, the expression of AMPK and P53 decreased and the number of autophagosomes decreased, demonstrating the potential of TUG1 to promote the differentiation of BMSCs into OBs by regulating the AMPK/mTOR/autophagy axis. 119 Non-imprinted in Prader-Willi/Angelman syndrome region protein 2 (NIPA2) is a highly selective magnesium transporter. The overexpression and silencing of NIPA2 gene indicated that NIPA2 regulates PINK1/Parkin-mediated mitophagy through the PGC-1/FoxO3a pathway, affecting the function of OBs.…”
Section: Regulation Of Protein Molecules On Autophagy Of Obs and Ocsmentioning
confidence: 99%
“… [ 116 ] TUG1 BMSCs AMPK/mTOR signaling pathway Silencing TUG1 gene inhibits autophagy and osteoblast differentiation via AMPK/mTOR signaling pathway. [ 119 ] NIPA2 hFOB1.19 PINK1/Parkin signaling pathway Silencing NIPA2 gene enhanced PINK1/Parkin-mediated mitophagy and down-regulated the function of osteoblasts. [ 73 ] c-Fos BMMs Beclin1, PI3K/Akt, TAK1/S6 signaling pathway Overexpression of the c-Fos gene reverses OPG-mediated inhibition of osteoclastogenesis by activating Beclin1-induced autophagy [ 121 ] KIF2 RAW264.7 Beclin-1 signaling pathway KIF2 knockdown significantly increases Beclin-1 expression, thereby regulating autophagy and osteoclast differentiation [ 123 ] JNK1 RAW264.7 Beclin-1/Bcl2 signaling pathway Silencing of the JNK1 gene reduces autophagy and osteoclastogenesis, and Beclin-1 silencing blocks JNK1-promoted autophagy responses in OCPs [ 125 ] TET2 RAW264.7 Beclin-1/Bcl2 signaling pathway Knockdown of Tet2 gene increases Bcl2 expression and decreases Beclin-1-dependent autophagy to reduce osteoclast differentiation [ 126 ] P2X7R BMMs Ca 2+ /Calcineurin/NFATc1 signaling pathway Knockdown of P2X7R gene inhibits Ca 2+ /Calcineurin/NFATc1 inhibits autophagy and osteoclast bone resorption [ 128 ] TRPV4↓ RAW264.7 Ca 2+ /Calcineurin/NFATc1 signaling pathway Knockdown of TRPV4 gene inhibits autophagy via Ca ...…”
Section: Regulation Of Protein Molecules On Autophagy Of Obs and Ocsmentioning
confidence: 99%
“…TUG1 expression levels are downregulated in patients with osteoporosis, suggesting possible involvement in osteogenesis [9]. Another study revealed that TUG1 functioned as a positive regulator in osteogenic differentiation of BMSCs through the AMPK/mTOR/autophagy pathway [11]. However, little is known about the role of TUG1 in osteo/odontogenic differentiation of hDPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, TUG1 could promote cell proliferation and invasion by modulating the miR-145-5p-TRPC6 regulatory axis in colorectal cancer [8]. Recently, emerging evidence suggested that TUG1 was crucial to osteogenic lineage commitment of several mesenchymal stem cells (MSCs) [9][10][11]. TUG1 expression levels are downregulated in patients with osteoporosis, suggesting possible involvement in osteogenesis [9].…”
Section: Introductionmentioning
confidence: 99%